Secured multi door access system as a web application / Nor Shamshillah Kamarzaman ... [et al.] - Kamarzaman, Nor Shamshillah; Abdul Jamil, Norhayati; Azizan, Noraliza; Jaafar, Jaaz Suhaiza; Ahmad Nazri, Muhamad Syafiq (2021)
In the era of Internet of Things (IoT) nowadays people are connected through many mobile devices remotely. Internet connectivity has provided major benefits to modern society in terms of sharing and accessing information. Increasing numbers of mobile devices operating worldwide, has shown that people use mobile devices for many activities in their daily lives. Mobile devices are used in many IoT appliances and systems. Our previous study has focused on smartphone utilization as a tool to unlock doors, where we create a secured door access system on smartphones, and use it as a key to unlock doors connected through secured Wi-Fi connection. However, since there is a limitation on mobile applications that is dependent on the type of operating system, we create a new system which is a web application where it is multi-platform and can be accessed with any mobile devices. Users can unlock the door using their registered accounts where admin is able to set the authorization of the user to which door they can unlock.